Addressing Known hypertensive disOrders of pregnancy in woMen of African descent in Canada (AKOMA): protocol for a mixed method study - Baiden, Deborah; Nerenberg, Kara; Hillan, Edith M.; Dogba, Maman Joyce; Parry, Monica (Frontiers in Cardiovascular Medicine, 2024)
BackgroundHypertensive disorders of pregnancy (HDP) predispose a woman to maternity-related cardiovascular morbidity and mortality. However, there is limited literature on HDP among women of African descent in Canada.Methods and designA convergent mixed-method study will be used to investigate the intersection of self-reported HDP risks in women of African descent in Canada with a history of a HDP (quantitative, cross-sectional survey) and explore the perception and experiences of women of African descent living in Canada with a history of a HDP in relation to the intersection of risk factors (critical qualitative inquiry, interviews). Quantitative analysis will use SPSS V. 27.0 and thematic analysis will be conducted using NVivo V. 12. A joint display will be used to combine the quantitative and qualitative results.DiscussionThrough the lens of intersectionality, the proposed study aims to provide a comprehensive understanding of the intersection of risks for HDP among women of African descent in Canada with a history of HDP. Furthermore, results could inform future strategies to reduce cardiovascular disease risks. Trial Registration NumberThis is registered in the Open Sciences Framework as follows: https://doi.org/10.17605/OSF.IO/R6CKY.